The U.S. Health Care Industry : Performance and Issues. (IMF Working Papers; Working Paper ;, 1990)
This paper describes how economic behavior in the market for health care in the United States is influenced by a range of impediments to the functioning of the price mechanism which impart an upward bias to health care costs and imply efficiency losses. The paper also considers how to reform the health care sector, with particular emphasis on finding a way of resolving the dilemma posed by the tradeoff between the risk spreading afforded by insurance and establishing appropriate incentives to restrain expenditures.